Hemolytic disease of the new-born due to ABO incompatibility - Kattimani, Vijaya S.; C. B., Ushakiran (International Journal of Contemporary Pediatrics, 2018)
Background: Better understanding of the clinical characteristics of HDN due to ABO incompatibility helps to optimise care. The objective of this study was to investigate the clinical manifestations and outcome of treatment modalities. Methods:This study was a hospital based cross sectional study conducted in the neonatal unit of Cheluvamba hospital attached to Mysore Medical College and Research Institute. A total of 50 neonates with blood group A or B born to mothers with blood group O; with jaundice and or anemia were enrolled during the period from January 2015 to December 2015. The various maternal and neonatal parameter and their association with development of jaundice and or anemia was studied. The outcome of treatment modalities was studied. Results: Out of 50 ABO Incompatible neonates 24 (48%) were male and 26 (52%) were female. The percentage of O–A and O–B incompatible neonates were 38% (19) and 72% (31), respectively. Jaundice was detected within the first 24 hours in 6% and 18% neonates had anemia. The mean age of presentation was 2.9±0.89 days. The various maternal and neonatal factors had no significant association with development of jaundice and or anemia due to ABO Incompatibility. The mean initial Indirect Bilirubin was 21.26±3.97, initial hemoglobin was 14.3±2.31 and the mean Reticulocyte count was 16.6±5.3. Total 22 (44%) neonates had laboratory evidence of hemolysis (microspherocytosis). DCT was positive in 4 (8%) neonates. The main clinical manifestation was jaundice and was treated with phototherapy in 49 (98%) of the cases. The mean duration of phototherapy was 53.84±9.82 hours. Only one infant required exchange transfusion and on follow up had no neurological sequelae. The mean total duration of stay was 3.6±1.2 days. There was no significant difference in the HDN due to either O–A or O–B incompatibility. Conclusions:Early identification of high risk neonates with ABO Incompatibility, diagnosis and early intervention can reduce morbidity and mortality.